KEPEMIMPINAN DAN MANAJEMEN DALAM PENDIDIKAN ISLAM: ANALISIS DALIL NAQLI TENTANG KEPEMIMPINAN - Siti Arifah; Sirli Yuliani; Fitriani Fitriani; Ansori Ansori; Iwan Aprianto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Leadership is a key factor in ensuring the effectiveness of Islamic educational institutions. In the Islamic perspective, leadership is not merely the ability to manage an organization but also a trust (amanah) that must be exercised based on the values of the Qur'an and Hadith. This study aimed to analyze the concept of leadership in Islamic education from the perspective of naqli (revealed) sources and to identify the leadership values that serve as the foundation for educational leadership and management. This research employed a qualitative approach using a library research method. Data were collected from the Qur'an, Hadith, books, and relevant scientific journal articles and analyzed through content analysis involving data reduction, data presentation, interpretation, and conclusion drawing. The findings reveal that Islamic educational leadership is founded upon five core values: trustworthiness (amanah), justice, consultation (shura), exemplary conduct, and responsibility. These values function not only as ethical principles but also as practical guidelines for educational management, including planning, decision-making, implementation, and evaluation. The study concludes that integrating Qur'anic and Prophetic leadership values into educational management provides a relevant framework for developing professional, ethical, and value-based leadership capable of addressing contemporary educational challenges. ABSTRAK Kepemimpinan merupakan faktor strategis dalam keberhasilan penyelenggaraan pendidikan Islam, tetapi kajian yang mengintegrasikan landasan normatif Al-Qur'an dan Hadis dengan praktik manajemen pendidikan masih terbatas. Penelitian ini bertujuan menganalisis konsep kepemimpinan dalam pendidikan Islam berdasarkan dalil-dalil naqli serta mengidentifikasi nilai-nilai kepemimpinan yang terkandung di dalamnya sebagai landasan pengembangan kepemimpinan dan manajemen pendidikan Islam. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Data diperoleh dari Al-Qur'an, Hadis, buku, artikel jurnal, dan literatur relevan, kemudian dianalisis menggunakan teknik content analysis. Hasil penelitian menunjukkan bahwa kepemimpinan pendidikan Islam berlandaskan lima nilai utama, yaitu amanah, keadilan, musyawarah, keteladanan, dan tanggung jawab. Kelima nilai tersebut tidak hanya memiliki dimensi normatif, tetapi juga terintegrasi dengan fungsi perencanaan, pengorganisasian, pengambilan keputusan, pelaksanaan program, dan evaluasi dalam manajemen pendidikan. Penelitian ini menyimpulkan bahwa integrasi nilai-nilai kepemimpinan berbasis dalil naqli dengan fungsi manajemen pendidikan memberikan landasan konseptual bagi pengembangan kepemimpinan pendidikan Islam yang profesional, berintegritas, dan adaptif terhadap tantangan pendidikan kontemporer.